Evaluation of the novel total artificial heart Realheart in a pilot human fitting study. Issue 2 (2nd September 2019) - Pieper, Ina Laura; Sonntag, Simon Johannes; Meyns, Bart; Hadi, Hind; Najar, Azad
Abstract: Heart failure affects >26 million patients worldwide. Current cardiac devices save lives, but patients suffer complications. Hence, improved devices are needed. Realheart TAH is a novel total artificial heart which has shown promising results in acute pig studies. However, the device design needed to be evaluated in humans. Virtual implantations demonstrated the device fits in two of three patients, but that there was some interference with the left lung. Herein, we used an innovative 3D‐printed model with swivelling device components to test the device in human cadavers. Our new method demonstrated how to optimize design to improve the surgical fit.